Peran Badan Pengawas Pemilihan Umum Kabupaten Sidoarjo Terhadap Tindakan Pencegahan Dan Penindakan Praktik Money Politics - Nugroho, Haikal Dwi; Arundinasari, Indira (Yayasan Sagita Akademia Maju, 2025)
aims to identify the role of the Sidoarjo Regency General Election Supervisory Agency (Bawaslu) in preventing and cracking down on the practice of money politics during the 2024 Election. Using Biddle's role indicator theory approach, this research examines three main aspects, namely expectations, norms and forms of behavior in carrying out election supervision duties. The research method used is a qualitative approach with descriptive methods. Data was obtained through semi-structured interviews with various related parties, including the Chair of the Sidoarjo Regency KPU, the Chair of the PPK, and the voting public. Apart from that, this research also uses literature study to strengthen the analysis. The data analysis technique refers to the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions. The results of the research show that Bawaslu of Sidoarjo Regency has carried out its role well in efforts to prevent and prosecute money politics. From the aspect of hope, there are high expectations from the community and related institutions for Bawaslu to be more proactive in socializing and enforcing the law. In terms of norms, Bawaslu is proven to maintain neutrality and transparency in carrying out its duties, which increases public confidence in elections. Meanwhile, in terms of behavior, Bawaslu has carried out investigations and taken action against alleged money politics practices, which has had a deterrent effect on perpetrators.